OsmiR396d Affects Gibberellin and Brassinosteroid Signaling to Regulate Plant Architecture in Rice. Issue 1 (27th November 2017) - Tang, Yongyan; Liu, Huanhuan; Guo, Siyi; Wang, Bo; Li, Zhitao; Chong, Kang; Xu, Yunyuan
Abstract : The microRNA396d connects OsBZR1 with OsGRFs to regulate the signal of brassinosteroid and gibberellin for controlling the key agriculture yield traits in rice. Abstract: Genetic improvement of plant architecture is one of the strategies for increasing the yield potential of rice ( Oryza sativa ). Although great progress has been made in the understanding of plant architecture regulation, the precise mechanism is still an urgent need to be revealed. Here, we report that over-expression of OsMIR396d in rice results in semidwarf and increased leaf angle, a typical phenotype of brassinosteroid (BR) enhanced mutant. OsmiR396d is involved in the interaction network of BR and gibberellin (GA) signaling. In OsMIR396d over-expression plants, BR signaling was enhanced. In contrast, both the signaling and biosynthesis of GA were impaired. BRASSINAZOLE-RESISTANT1, a core transcription activator of BR signaling, directly promoted the accumulation of OsmiR396d, which controlled BR response and GA biosynthesis by regulating the expression of different target genes respectively. GROWTH REGULATING FACTOR 6, one of OsmiR396d targets, participated in GA biosynthesis and signal transduction but was not directly involved in BR signaling. This study provides a new insight into the understanding of interaction between BR and GA from multiple levels on controlling plant architecture.